PENGARUH INVESTASI TERHADAP PDRB SEKTOR PERTANIAN DI KALIMANTAN BARAT - SURATMAN, SURATNA; YURISINTHAE, ERLINDA; SUDRAJAT, JAJAT (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
Investment is one of the production factors which role as an economic mobiliser in West Kalimantan. Investment could encourage the increase of production in agricultural sector, which impactto the increasing of economic growth. The role of the development in agricultural sector towards the regions economic could be seen from the contribution of GDP in agricultural sector. Some investment sources, including Domestic and Foreign Investments could push the increase of economy in a region. The research is motivated by the fact that the contribution of agricultural sector to GDP in West Kalimantan which has decreased over the years and followed by an investment value of both domestic and foreign investments which are always fluctuate.The research aims to find out the influence of Domestic and Foreign Investments towards GDP in agricultural sector in West Kalimantan in 1993-2013. The research uses continouse data in 1993-2013 with the data analysis technique, which uses multiple linear regression with OLS method.The result of this research indicates that Domestic Investment and Foreign Investment gives a positive impact to GDP in agricultural sector. The support of Domestic Investment towards economic growth will increase the numbers of GDP in agricultural sector in West Kalimantan. Also Foreign Investment in agricultural sector gives a positive contribution and it means that the higher Foreign Investment in agricultural sector makes the numbers of GDP in agricultural sector increase in West Kalimantan.